2013
DOI: 10.1096/fj.13-227694
|View full text |Cite
|
Sign up to set email alerts
|

Paternal lifestyle as a potential source of germline mutations transmitted to offspring

Abstract: Paternal exposure to high levels of radioactivity causes heritable germline minisatellite mutations. However, the effect of more general paternal exposures, such as cigarette smoking, on germline mutations remains unexplored. We analyzed two of the most commonly used minisatellite loci (CEB1 and B6.7) to identify germline mutations in blood samples of complete mother-father-child triads from the Norwegian Mother and Child Cohort Study (MoBa). The presence of mutations was subsequently related to general lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…Smoking is known to cause genetic and epigenetic damage to spermatozoa, which are transmissible to offspring and have the potential to induce developmental abnormalities. 4,5,7,9,[24][25][26][27][28][29] In utero smoking exposure of fathers could influence primordial germ cell development. 3 A prepubertal vulnerability window could be related to de novo DNA methylation occurring during primordial germ cell differentiation to spermatogonia.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is known to cause genetic and epigenetic damage to spermatozoa, which are transmissible to offspring and have the potential to induce developmental abnormalities. 4,5,7,9,[24][25][26][27][28][29] In utero smoking exposure of fathers could influence primordial germ cell development. 3 A prepubertal vulnerability window could be related to de novo DNA methylation occurring during primordial germ cell differentiation to spermatogonia.…”
Section: Discussionmentioning
confidence: 99%
“…We also recommend that additional dose-response studies and analysis of other mutagens be conducted to establish fully the sensitivity of the assay for germ-cell mutation analysis. This method can be applied potentially to environmental biomonitoring using sentinel species and to human populations to assess the effects of variables that influence heritable mutagenesis [1,4,33,[60][61][62][63][64][65][66]. Our new method expands our ability to detect mutations in germ cells, but we must consider the diverse types of mutation mechanisms and continue to expand the mutational landscape that we can capture in toxicological screening [67].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing recognition that environmental and lifestyle variables may contribute to increased heritable-mutation burden and adverse effects in the descendants of exposed males [1][2][3][4][5]. Applications of high-throughput genomics technologies in human Abbreviations: ESTRs, expanded simple tandem repeats; SM-PCR, singlemolecule PCR; ENU, N-ethyl-N-nitrosourea; BaP, benzo[a]pyrene; TGR, transgenic rodent gene mutation assay.…”
Section: Introductionmentioning
confidence: 99%
“…Potential regulatory roles during fertilization and embryogenesis have been suggested for the collection of ncRNAs including confrontation and consolidation of the maternal and paternal genome during fertilization (reviewed in Bourc'his and Voinnet 2010; Krawetz et al 2011;Jodar et al 2013). Several recent studies have suggested that environmental changes may be transmitted to the offspring through spermatozoa, influencing their fertility or health (reviewed in Ng et al 2010;Rando 2012;Linschooten et al 2013;Selvaraju et al 2014). These include a predisposition to diabetes or perhaps even depression in the offspring which can reflect diet or a previous response of the father to traumatic stress (Carone et al 2010;Ng et al 2010;Rando 2012;Gapp et al 2014).…”
Section: Spermatozoal Retained Rnasmentioning
confidence: 99%